2015
DOI: 10.3389/fonc.2015.00027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Helical TomoTherapy for the Focal Hypofractionated Treatment of Limited Brain Metastases in the Initial and Recurrent Setting

Abstract: Background: Whole-brain radiation therapy (WBRT), stereotactic radiosurgery (SRS), or both are commonly employed in the treatment of limited brain metastases in the initial or recurrent setting. Hypofractionated partial volume irradiation is also employed, however, published experience using helical TomoTherapy (HT) for this purposes is limited. We reviewed our institutional experience to assess patient selection factors, fractionation scheme, and outcomes associated with this technique.Methods: A retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…• Índices dosimétricos atingidos no planejamento similares aos obtidos por outros sistemas já consolidados (ELSON et al, 2015;SOISSON;MP;WA, 2011).…”
Section: Acelerador Linear Helicoidal Ou Em Anelunclassified
“…• Índices dosimétricos atingidos no planejamento similares aos obtidos por outros sistemas já consolidados (ELSON et al, 2015;SOISSON;MP;WA, 2011).…”
Section: Acelerador Linear Helicoidal Ou Em Anelunclassified
“…Helical radiotherapy requires special consideration, as the MLC leaf width might be larger compared to the gantrybased MLC systems used for SRS and FSRT (i.e., 6.25 mm) but the delivery technique is different (helical) and it is in fact claimed to be used clinically for SRS and FSRT (e.g., [149][150][151][152][153][154]). However, in connection with helical treatment, especially for SRS, the inherent coplanarity of this modality (and for others, too) might be an additional disadvantage [155][156][157].…”
Section: Helical and Coplanar-only Radiotherapymentioning
confidence: 99%
“…The continuous gantry rotation, combined with couch translation, and the non-isocentric approach could in fact lead to significant time saving when compared with other techniques: multiple lesions could be treated within a single delivery and therefore it would not require new patient set-up for each target. Nevertheless, only few works (Baisden et al 2007, Levegrün et al 2013, Nagai et al 2014, Barra et al 2015, Elson et al 2015 reported the employment of HT for the treatment of brain metastases.…”
Section: Introductionmentioning
confidence: 99%